Small-sided games versus interval training in amateur soccer players: Effects on the aerobic capacity and the ability to perform intermittent exercises with changes of direction - Dellal, A.; Varliette, C.; Owen, A.; Chirico, E. N.; Pialoux, V. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to compare the effects of small-sided games (SSGs) in soccer versus high-intensity intermittent training (HIT) on a continuous aerobic test (Vameval) and the performance in an intermittent test with changes of direction (CODs; 30-15 intermittent fitness test [30-15IFT]). Twenty-two amateur soccer players (mean age ± SD: 26.3 ± 4.7 years) were assigned to 3 different groups for 6 weeks: SSG group (n = 8), HIT group (n = 8), and control group (CG; n = 6). In addition to the usual technical and tactical sessions and competitive games, the SSG group performed 9 sessions of 2 versus 2 and 1 versus 1 SSGs, whereas the HIT group performed 9 sessions of intermittent runs in the form of 30 seconds of effort interspersed with 30 seconds of passive recovery (30s-30s), 15s-15s, and 10s-10s. The HIT and SSG groups showed performance improvements in the Vameval test (5.1 and 6.6%, respectively) and the 30-15IFT intermittent test with CODs (5.1 and 5.8%, respectively), whereas there was no change in the performance of the CG. Players from HIT and SSG groups showed similar increase in their performance in the 30-15IFT and the Vameval tests during the 6-week training period, especially with an increase significantly different to that in a traditional training as in the CG (p < 0.05). This investigation demonstrates that both SSG and HIT interventions are equally effective in developing the aerobic capacity and the ability to perform intermittent exercises with CODs in male amateur soccer players. Furthermore, these 2 methods of training applied during the 6 weeks induce similar effect on the recovery capacity and on the ability to repeat directional changes of 180°. Coaches will now be able to choose between these two methods according to the objective of the training and to optimize the training.